The Transnational Dimension of Cyber Crime and Terrorism. - Goodman, Seymour E. (Hoover national security forum series., 2001)
In December 1999, more than forty members of government, industry, and academia assembled at the Hoover Institution to discuss this problem and explore possible countermeasures. The Transnational Dimension of Cyber Crime and Terrorism summarizes the conference papers and exchanges, addressing pertinent issues in chapters that include a review of the legal initiatives undertaken around the world to combat cyber crime, an exploration of the threat to civil aviation, analysis of the constitutional, legal, economic, and ethical constraints on use of technology to control cyber crime, a discussion.